Analisis Problem Pembelajaran Matematika SMP “X” Kota Tangerang Selatan - Widiyanti, Whida (MASALIQ, 2024)
This study is aimed at solving problems from the obstacles faced during learning. This research was carried out at SMP "X" Pondok Cabe Ilir, South Tangerang. This case study research was carried out during the learning process for 6 meetings in three weeks. The subject of this research was carried out in grade VII for the 2023/2024 school year with 22 students. The data used in this study was by collecting interview information, and observations in the classroom. This study uses qualitative descriptive by using the case study method, where observation, data collection, data analysis and reporting results are carried out. The results of the study show that there are several problems in mathematics learning that teachers face during the learning process, namely that students experience difficulties in understanding concepts, skill difficulties, and problem-solving difficulties. Difficulty understanding concepts from other students, namely, amplifying formulas. In the problem of skill difficulties, students experience difficulties in numeracy skills. In problem solving, students have difficulty solving problems in story problems. In addition to experiencing difficulties in learning, there are several other factors that make students experience difficulties in learning, including a lack of variety in the use of media or learning tools, a lack of motivation in students to learn more outside of class hours, and a lack of support from parents in accompanying students to study at home.